2007
DOI: 10.1007/s10554-006-9202-8
|View full text |Cite
|
Sign up to set email alerts
|

Renal perforation and retroperitoneal hematoma: an unusual complication following cardiac catheterization

Abstract: Retroperitoneal hematoma (RPH) is a well-recognised, albeit rare complication of percutaneous transfemoral cardiac catheterization. We describe an unusual case of renal perforation and RPH following transfemoral cardiac catheterization for endomyocardial biopsy. Diagnosis was made based on multidetector computed tomography (MDCT) which clearly depicted active renal hemorrhage in short acquisition time. The case expands the spectrum of possible complications of percutaneous transfemoral cardiac catheterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
7
1
1
Order By: Relevance
“…2) Retroperitoneal hemorrhage related to renal artery injury, as demonstrated in the present case, is markedly rare, and only a few case reports have been published. 3,4) conducted. The blood examination 26 days after treatment suggested improvement (the Hb level, platelet count, BUN/ Cre value, and eGFR were 10.1 g/dL, 210,000/mL, 14.2/0.58 mg/dL, and 78 mL/min/L, respectively).…”
Section: Course Of Transarterial Embolizationmentioning
confidence: 99%
See 1 more Smart Citation
“…2) Retroperitoneal hemorrhage related to renal artery injury, as demonstrated in the present case, is markedly rare, and only a few case reports have been published. 3,4) conducted. The blood examination 26 days after treatment suggested improvement (the Hb level, platelet count, BUN/ Cre value, and eGFR were 10.1 g/dL, 210,000/mL, 14.2/0.58 mg/dL, and 78 mL/min/L, respectively).…”
Section: Course Of Transarterial Embolizationmentioning
confidence: 99%
“…Several studies reported complications, such as retroperitoneal hemorrhage, related to vascular injury on puncture or catheter guiding. [1][2][3][4] Prior to carotid artery stenting or coil embolization of cerebral aneurysms, majority of patients were administered two antiplatelet drugs orally, and thus, occurrence of vascular injury may lead to serious complications.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed physical examination and thorough history rarely lead to misdiagnosis of the condition (Peters et al, 2007). However, spontaneous retroperitoneal hemorrhage is a much less common distinct clinical entity that can be life-threatening.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its unfamiliar etiology, the hematomas origin might be spontaneous or iatrogenic, which could be secondary to endovascular trauma or the use of anticoagulation drugs during the procedure. Risk factors predisposing to retroperitoneal haemorrhage after percutaneous transfemoral cardiac intervention are the following: the female sex, low platelet count, sheath removal protocol, the use of hydrophilic guide wire [7] and post-procedure anticoagulation, presenting the greatest risk [8]. …”
Section: Introductionmentioning
confidence: 99%